Dissipative Approach in Analysis and Synthesis of Control System via Linear Matrix Inequalities - Asep Najmurrokhman (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2008)
This paper discusses about application of dissipative concept in dynamical systems for analysis and synthesis of control systems via linear matrix inegualities (LMIs). Motivated by dissipativity concept in mechanical and electrical circuit system, one could employ this concept to check stability and to design a controller of the underlying system. We derive the solvability condition of dissipativity for an output feedback LTI continuous system via LMIs. An algorithm to design such controller that satisfy the dissipativity of the system is also considered.